Assessing the origins, evolution and prospects of the literature on dynamic capabilities: A bibliometric analysis - Gema Albort-Morant; Antonio L. Leal-Rodríguez; Vicente Fernández-Rodríguez; Antonio Ariza-Montes (European Research on Management and Business Economics (ERMBE), 2018)
The purpose of this study is to serve as orientation and guidance to academics that are starting or currently developing their research within the field of dynamic capabilities, in order to enhance their knowledge about which are the key scientific journals, authors and articles shaping this topic. This paper presents a bibliometric analysis on dynamic capabilities, making use of the Web of Science database to perform it. This analysis comprises fundamental issues such as (i) the number of studies published per year, (ii) the countries with the highest rate of productivity, (iii) the most prolific and influential authors, (iv) assessment of studies citing dynamic capabilities, and (v) the most productive journals on dynamic capabilities and recent studies on this topic. Results reveal an exponential growth in the number of publications on dynamic capabilities for the 2000–2012 period. Although, since 2012 this growth has decelerated, the number of publications on this topic remains noteworthy. This study brings useful information for those academics and practitioners attempting to analyze and deepen within this particular field of research, at the same time that provides some insights concerning the future development and progress of the dynamic capabilities topic in the management, business and economics academic literature.
Keywords: M0; M1; M2; 650; Dynamic capabilities; Bibliometric analysis; Web of Science